1., (i) 10p - (3p - 4) = 4(p + 1) +9
Attachments:
![](https://hi-static.z-dn.net/files/d37/38833696124567efe423e20f027a1af8.jpg)
Answers
Answered by
1
Step-by-step explanation:
I hope will help you
please as Mark me brainlies
please follow me
thank
Attachments:
![](https://hi-static.z-dn.net/files/d69/e95600fb4497698c74442e30979791ae.jpg)
Answered by
2
Answer:
The value of p is 3
Step-by-step explanation:
10p-(3p-4)=4(p+1)+9
➡️10p-3p+4=4p+4+9
➡️7p+4=4p+13
➡️7p-4p=13-4
➡️3p=9
➡️p=9/3
➡️p=3
Please mark my answer brainliest answer and thanks me if it helps you
Similar questions